Enhanced SWIR absorption in chemical bath deposited PbS thin films alloyed with thorium and oxygen. Issue 91 (14th September 2016) - Templeman, Tzvi; Shandalov, Michael; Yahel, Eyal; Ezersky, Vladimir; Sarusi, Gabby; Golan, Yuval
Abstract : We report on chemically deposited thin films of PbS alloyed with thorium. Material properties, including the optical band gap, are shown to strongly depend on film composition, presenting a clear bowing behavior and enhanced SWIR absorption. Abstract : We report on chemically deposited thin films of PbS alloyed with thorium. Control over the thorium content in the films was achieved by lowering the solution pH and compensating by adding tri sodium citrate as a co-complexant. Homogeneous distribution of thorium was achieved, accompanied by substantial oxygen content, up to concentrations of 9 at% thorium and 20 at% oxygen. Regardless of these relatively high concentrations, a single phase of alloyed PbS was found in X-ray and electron diffraction, indicating complete solubility of the species within the lattice. Physical properties such as the optical band gap and transmission spectra showed a strong dependence on thorium content due to chemical variations and size dependent quantum confinement. This new system is a promising candidate for electro-optic applications due to ease of band-gap tuning and enhanced optical absorption in the short wave infrared (SWIR) range.